Postharvest performance of 17 apple accessions grown in NE Spain after long-term cold storage - Pierre Mignard; Rosa Giménez; María Angeles Moreno (Journal of Applied Botany and Food Quality, 2023)
In this work, 17 accessions from the Apple Germplasm Bank of the EEAD-CSIC were harvested and stored in a cold room for six months, at low temperature (1-1.5 °C) and controlled relative humidity (85-90%). The objective of this study was to evaluate differences among accessions at biochemical level between harvest and after long-term cold storage, defining their suitability for storage. Basic fruit quality parameters and antioxidant compounds were evaluated, and individual sugars and major organic acids were determined. A PCA was carried out explaining 70% of the total variability. ‘Evasni’ presented the best performance in postharvest after cold storage. The concentrations of organic acids and phenolic compounds, in general, decreased after long-term conservation. Triploid accessions with presence of russeting highlighted for their higher content in bioactive compounds even after cold storage. Nevertheless, the russeting seemed to be related to cell damages and increased chilling injuries such as browning or dehydration. Spanish accessions ‘Reneta’ and ‘Solafuente’ and other non-Spanish bred cultivars showed their suitability for conservation with no chilling injuries after long-term cold storage. The present work highlighted the interest of native accessions and non-Spanish cultivars to be considered in future breeding programs thanks to their best marketability and consumer accept- ability